The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.3390/biom12060783
|View full text |Cite
|
Sign up to set email alerts
|

Unique SMYD5 Structure Revealed by AlphaFold Correlates with Its Functional Divergence

Abstract: SMYD5 belongs to a special class of protein lysine methyltransferases with an MYND (Myeloid-Nervy-DEAF1) domain inserted into a SET (Suppressor of variegation, Enhancer of Zeste, Trithorax) domain. Despite recent advances in its functional characterization, the lack of the crystal structure has hindered our understanding of the structure-and-function relationships of this most unique member of the SMYD protein family. Here, we demonstrate the reliability of using AlphaFold structures for understanding the stru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 48 publications
0
4
0
Order By: Relevance
“…The prediction was obtained using the monomeric model of AlphaFold in default parameters. The predicted complex structure with the highest pLDDT value (87.86) was trusted with the highest confidence level and adopted for subsequent analyses 39 . And it was superimposed with the resolved complex structure of Cad23 NBM/Harmonin NTD (PDB ID: 2KBR ) for validation.…”
Section: Methodsmentioning
confidence: 99%
“…The prediction was obtained using the monomeric model of AlphaFold in default parameters. The predicted complex structure with the highest pLDDT value (87.86) was trusted with the highest confidence level and adopted for subsequent analyses 39 . And it was superimposed with the resolved complex structure of Cad23 NBM/Harmonin NTD (PDB ID: 2KBR ) for validation.…”
Section: Methodsmentioning
confidence: 99%
“…A caveat of our study is that our results are not fully transferable to neonatal hypoxic-ischemic brain injury as neuroprotection in that setting is achieved at 33.5°C and getting as low as 32°C is not recommended 10 . Another limitation of our study is that SMYD5 doesn´t have any known intrinsic DNA binding ability 45 , thus there must be another factor that recruits SMYD5 to the right sites. This could be addressed in future studies by exploring protein interactors of SMYD5 or with a more focused CRISPR-Cas9 library screening using a library only containing known transcriptional regulators.…”
Section: Limitations Of Studymentioning
confidence: 99%
“…X-ray crystallographic studies have been carried out for SMYD1 [ 29 , 63 ], SMYD2 [ 29 , 45 , 64 , 65 , 66 , 67 ], and SMYD3 [ 29 , 31 , 68 , 69 ]. At this time, no structural studies have been reported for SMYD4, but some work is underway for SMYD5 [ 70 ].…”
Section: Smyd-proteins Structure Function and Medicinal Potentialmentioning
confidence: 99%